Creative Innovation in the Work Process Affecting the Performance Effectiveness of Employees at Convenience Stores in the Bangkok Metropolitan Area: การสร้างสรรค์นวัตกรรมกระบวนการทำงานที่มีต่อประสิทธิผลการปฏิบัติงานของพนักงานร้านสะดวกซื้อในเขตกรุงเทพมหานคร - Muangjaroen, Jaruwan; Phasunon, Prasopchai (Journal of Applied Economics and Management Strategy, 2019)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาอิทธิพลของการสร้างสรรค์นวัตกรรมกระบวนการทำงานที่มีผลต่อประสิทธิผลการปฏิบัติงานของพนักงานร้านสะดวกซื้อในเขตกรุงเทพมหานคร และศึกษาความสอดคล้องของโมเดลการสร้างสรรค์นวัตกรรมกระบวนการทำงานที่มีผลต่อประสิทธิผลการปฏิบัติงานของพนักงานร้านสะดวกซื้อในเขตกรุงเทพมหานครกับข้อมูลเชิงประจักษ์ กลุ่มตัวอย่างได้แก่ พนักงานร้านสะดวกซื้อในเขตกรุงเทพมหานคร จำนวน 400 คน เครื่องมือวิจัย ได้แก่ แบบสอบถาม การวิเคราะห์ข้อมูลเชิงปริมาณใช้สถิติที่ใช้ในการวิเคราะห์ ได้แก่ ค่าร้อยละ ค่าเฉลี่ยเลขคณิต ค่าเบี่ยงเบนมาตรฐาน การวิเคราะห์ความสัมพันธ์ระหว่างตัวแปรอิสระโดยใช้ค่าสหสัมพันธ์เพียร์สัน และสถิติการวิเคราะห์โมเดลสมการโครงสร้าง ผลการวิจัยพบว่า โมเดลที่ผู้วิจัยได้ปรับปรุงและพัฒนาขึ้นมีความสอดคล้องกลมกลืนกับข้อมูลเชิงประจักษ์ โดยมีค่าดัชนีตรวจสอบความกลมกลืน ได้แก่ Chi-Square = 22.098, df = 24, P-Value = 0.573, Chi-Square/df = 0.920, SRMR = 0.003, GFI = 0.989, CFI = 1.000, RMSEA = 0.000 ประกอบด้วยการสร้างสรรค์นวัตกรรมมีอิทธิพลทางตรงต่อประสิทธิผลการปฏิบัติงาน และทางอ้อมต่อประสิทธิผลการปฏิบัติงานโดยผ่านกระบวนการทำงาน อย่าง มีนัยสำคัญทางสถิติที่ระดับ 0.01 คำสำคัญ: การสร้างสรรค์นวัตกรรม กระบวนการทำงาน ประสิทธิผลการปฏิบัติงาน Abstract The objectives of this research were to study the effectiveness of creative innovation in the work process affecting the performance effectiveness of employees at convenience stores in the Bangkok metropolitan area and to study the harmony of a model of creative innovation in the work process affecting the performance effectiveness of employees at convenience stores in Bangkok. The research applied quantitative methodology. The sample was comprised of 400 employees and the research tool was questionnaires. The quantitative data were statistically analyzed, including percentage, arithmetic mean, standard deviation, and the relationships between the independent variables, Pearson’s correlation, and structural equation modeling (SEM). The study revealed that the model, improved and developed by the researcher, was in harmony with the empirical data with Chi-Square = 22.098, df = 24, P-Value = 0.573, Chi-Square/df = 0.920, SRMR = 0.003, GFI = 0.989, CFI = 1.000, and RMSEA = 0.000. In addition, creative innovation has direct effect on the performance effectiveness and has indirect effect on the performance effectiveness passing through work process at 0.01 statistically significant level. Keywords: Creative Innovation, Work Process, Performance Effectiveness